Evaluating the costs and benefits of pneumococcal vaccination in adults. (1st February 2017) - Porchia, Barbara Rita; Bonanni, Paolo; Bechini, Angela; Bonaccorsi, Gugliemo; Boccalini, Sara
ABSTRACT: Introduction: Pneumococcal infection is a public health concern that disproportionately affects the young, the elderly, and the immunocompromised. There is an open debate on the implementation of polysaccharide and/or conjugate vaccines for pneumococcal diseases in adults and the elderly in many countries. The aim of this paper is to systematically review the economic profile of pneumococcal vaccines in adults in terms of costs and benefits. Areas covered: The search for economic studies on pneumococcal vaccination was carried out in Pubmed, Embase, Scopus, and the HTA and NHS EED databases and through a manual search in journals dealing with economic evaluations. We included original articles and reviews with economic evaluation of polysaccharide 23-valent (PPV23) and/or conjugate pneumococcal vaccine 13-valent (PCV13) use in adults, the elderly, and at-risk groups to provide a systematic review of economical evaluation. Expert commentary: Pneumococcal vaccination is strongly recommended for all adults, especially subjects at risk and the elderly. Pneumococcal vaccination with PCV13 or PPV23 in adults is good value for money and should be a priority for the decision-makers. The main issue is how vaccination could be offered.